Hubungan Religiusitas dengan Kesehatan Mental pada Populasi Dewasa Muda Muslim di Indonesia (Jurnal Ilmiah Psikologi MIND SET, 2023)
Religiosity is often associated with the good and bad condition of an individual's mental health so a lot of negative stigma arises on mental health issues. This study aims to scientifically prove the relationship between religiosity and mental health. This research method uses a quantitative method with an accidental sampling technique. To measure religiosity, the Muslim Religiosity Scale was used and to measure mental health, the Depression, Anxiety, Stress Scale 21 (DASS-21) was used. This study involved 133 participants from 13 provinces in Indonesia with 19.50% male participants and 80.50% female participants. Based on the results of the Paired Sample T-test, the results showed that there was no significant relationship between religiosity and the symptoms of mental health disorder, the correlation of religiosity and depression with r = -0.42; p > 0.05, with anxiety r = -0.29; p > 0.05, and with stress r = -0.36; p > 0.05. Based on the results of the study, we can interpret that the individual mental health aspect does not have a significant relationship with the high or low level of religiosity.